ROBOTIC PRODUCTION IN MECHANICAL ENGINEERING: ADVANTAGES AND DISADVANTAGES - Qosimova Zamira Medatovna; Uraimov Mukhammaddiyor Bahodir ogli (Zeta Repository, 2023)
This article discusses the topic of robotic production in mechanical engineering. In the modern world, automation of production processes with the help of robots is becoming more and more popular, and mechanical engineering is no exception. The article describes the advantages and disadvantages of robotic production in mechanical engineering, and also analyzes the impact of such automation on productivity, quality and cost of production.